ESTIMATION OF PREVALENCE, EFFECT AND COST OF MASTITIS ON SIMMENTAL DAIRY FARMS OF DIFFERENT SIZES - Gantner, Vesna; Jožef, Ivana; Gantner, Ranko; Steiner, Zvonimir Steiner; Zmaić, Luka; Solić, Dragan; Potočnik, Klemen (Economics of Agriculture, 2023)
Mastitis, a production disease highly prevalent in dairy farming, poses a significant challenge to farmers. It is responsible for decreased milk production, reduced milk quality, and increased treatment costs. Thus, early detection and prompt treatment are essential to prevent the infection and minimize the mastitis impact. This study aimed to determine how farm size affects the prevalence, effect, and cost of mastitis. Therefore, a total of 4,922,751 test-day records for dairy Simmental cows collected in the period 2005-2022 were analysed. Results showed that mastitis was most prevalent among small farms, which also exhibited a lower total increase in milk production. In contrast, the highest prevalence of healthy cows was observed at large farms, with the highest total increase in milk production.